Neuromancer - Gibson, William, 1948-; Harper Collins (London : Voyage, 1995)
Presents a twentieth-anniversary edition of the 1984 novel in which Case, a nerve-damaged data thief, is recruited by a new employer for a last-chance run against a powerful artificial intelligence.
Adult
Keywords: Business intelligence -- Fiction; Computer hackers -- Fiction; Conspiracies -- Fiction; Information superhighway -- Fiction; Nervous system -- Wounds and injuries -- Fiction; Espionage -- Fiction; Internet -- Fiction; Science fiction; Japan -- Fiction